Green Tea (EGCG) Decreases Malondialdehide In Oxidative Stress Exposure To Psychological Stress - Priaminda, M Dodi F; Wirjatmadi, Bambang; Purwanto, Bambang; Adriani, Merryana (Health Notions, 2018)
-